Consistent Intertemporal Decision Making - Blackorby, Charles; Nissen, David; Primont, Daniel; Russell, R. Robert (Review of Economic Studies, 1973)
Charles Blackorby, David Nissen, Daniel Primont, R. Robert Russell; Consistent Intertemporal Decision Making12, The Review of Economic Studies, Volume 40, Issue